A manifold design problem for a plate-fin microdevice to maximize the flow uniformity of system. (April 2016) - Huang, Cheng-Hung; Wang, Chun-Hsien; Kim, Sin
Highlights: A manifold design problem for flow rate uniformity is examined in this study. Two third-order-polynomial are used to simulate the shapes for manifolds. The LMM is then applied to determine the optimal design variables. The results obtained from the LMM are justified based on numerical experiments. The present design has better system uniformity than previous studies. Abstract: An optimum design problem to determine the optimum shapes for three-dimensional manifolds of plate-fin microdevice for the best system uniformity of flow ratios is examined in this study. The Levenberg–Marquardt Method (LMM) and a general purpose commercial code CFD-ACE+ are utilized to minimize both the system non-uniformity and manifold areas of the microdevice. Two third-order-polynomial functions are used to simulate the boundary shapes for inlet and outlet manifolds, and four different optimization design problems are examined to demonstrate the validity of the present study. The results obtained from the LMM are justified based on numerical experiments, and when applying two third-order-polynomial functions to construct the shapes of manifolds, the designed plate-fin microdevice always has better system uniformity than the design with linear lines in constructing the shapes of manifolds since a 12.08% improvement for the system non-uniformity in the present design, Type OPT4, can be achieved when comparing with the previous optimal design, Type B-O609.